Alien Intelligence. - Bailly, Sharon & Christian; Beloff, Zoe; Feingold, Ken; Hildebrand, Christoph; Hoberman, Perry; Holland, Owen; Huhtamo, Erkki; Hébert, Jean-Pierre; Iwai, Toshio; Kluitenberg, Eric; Lunenfeld, Peter; Manovich, Lev; et al. (Helsinki : KIASMA Museum of Contemporary Art, 2000)
The exhibition, curated by media scholar Erkki Huhtamo, investigates the impact of digital technology on culture as seen and interpreted by artists. Participating in Alien Intelligence there are major media artists from different parts of the world : the United States, Canada, Europe and Japan. Many of the works have been commissioned especially for this exhibition and will be experienced for the first time at Kiasma. To provide a historical perspective for the artists' visions, the exhibition also contains a Media-Archeological gallery of historical artefacts.
Beloff, Zoe ; Coenen, Arno ; Bosma, René ; Csikszentmihályi, Chris ; Feingold, Ken ; Hébert, Jean-Pierre ; Hildebrand, Christoph ; Hoberman, Perry ; Troy Innocent ; Iwai, Toshio ; Prophet, Jane ; Riches, Martin ; Rinaldo, Kenneth E. ; Roberts, Sara ; Rokeby, David ; Sommerer, Christa ; Mignonneau, Laurent ; Taanila, Mika
biog., ind. tent., gr. tent., bibliog. p. 138-162
Engels & Fins
Alien Intelligence, KIASMA (Museum of Contemporary Art) Helsinki, 12.2. - 28.5.2000
boek